Shipboard sunphotometer measurements of aerosol optical depth spectra during ACE-2 - Livingston, J.M.; Kapustin, V.; Schmid, B.; Russell, P.B.; Durkee, P.A.; Bates, T.S.; Quinn, P.K. (1998)
During the North Atlantic Regional Aerosol Characterization Experiment (ACE-2) held in summer 1997, the NASA Ames six-channel airborne tracking sunphotometer (AATS-6) was operated aboard the R/V Vodyanitskiy in the eastern Atlantic Ocean off the coast of Portugal and North Africa. This instrument measures the direct beam solar transmission through the earth’s atmosphere in six narrow bandpass regions at wavelengths centered between 380.7 and 1020.7 mn. Aerosol optical .depth spectra derived from ACE-2 measurements acquired during a variety of lower tropospheric aerosol loading conditions will be discussed. Comparisons with coincident optical depth data derived from airborne and/or satellite radiometer measurements will also be shown.